The use of eculizumab in ventilator‐dependent myasthenia gravis patients. Issue 2 (9th June 2021) - Usman, Uzma; Chrisman, Christina; Houston, Drew; Haws, Clara Chow; Wang, Alan; Muley, Suraj
Abstract: Introduction/Aims: Eculizumab has been shown to be efficacious in acetylcholine receptor antibody–positive (AChR + ) Myasthenia Gravis Foundation of America (MGFA) class II, III, and IV generalized myasthenia gravis (gMG) patients. However, it has not been studied in MGFA class V gMG patients. Methods: We report three AChR +, refractory, MGFA class V gMG patients treated with eculizumab. MGFA class, MG‐Composite (MGC) score and MG Activities of Daily Living (MG‐ADL) score were assessed before and after eculizumab. Results: Two of three gMG patients, refractory to intravenous immunoglobulin, plasmapheresis, prednisone, and (in one case) rituximab, showed a robust response to eculizumab with marked improvement in MGFA, MG‐ADL, and MGC measures. The third patient showed a partial response to eculizumab but remained on noninvasive ventilation and gastrostomy intubation. Patients 1 and 2 achieved minimal manifestation status at week 4 and week 6, respectively, and showed continued improvement on MG‐ADL and MGC scores through weeks 55 and 43, respectively, with eculizumab. The third patient showed a partial response at week 10, followed by a slight decline in his MG‐ADL score, but noted a slow but an incomplete improvement afterward on MG‐ADL and MGC scores, possibly due to delayed eculizumab infusion. Discussion: Eculizumab may play a role in the treatment of patients with MGFA class V, refractory gMG. Larger studies are required to provide further evidence.